Genetic Deficiency of MicroRNA‐15a/16‐1 Confers Resistance to Neuropathological Damage and Cognitive Dysfunction in Experimental Vascular Cognitive Impairment and Dementia. Issue 17 (11th April 2022) - Zhou, Chao; Sun, Ping; Xu, Yang; Chen, Yuang; Huang, Yixian; Hamblin, Milton H.; Foley, Lesley; Hitchens, T. Kevin; Li, Song; Yin, Ke‐Jie
Abstract: Chronic cerebral hypoperfusion‐derived brain damage contributes to the progression of vascular cognitive impairment and dementia (VCID). Cumulative evidence has shown that microRNAs (miRs) are emerging as novel therapeutic targets for CNS disorders. In this study, it is sought to determine the regulatory role of miR‐15a/16‐1 in VCID. It is found that miR‐15a/16‐1 knockout (KO) mice exhibit less cognitive and sensorimotor deficits following VCID. Genetic deficiency of miR‐15a/16‐1 in VCID mice also mitigate myelin degeneration, axonal injury, and neuronal loss. Mechanistically, miR‐15a/16‐1 binds to the 3'‐UTR of AKT3 and IL‐10RA. Genetic deletion of miR‐15a/16‐1 increases AKT3 and IL‐10RA expression in VCID brains, and intranasal delivery of AKT3 and IL‐10RA siRNA‐loaded nanoparticles partially reduce brain protection and cognitive recovery in miR‐15a/16‐1 KO mice after VCID. In conclusion, the miR‐15a/16‐1‐IL/10RA/AKT3 axis plays a critical role in regulating vascular brain damage and cognitive decline after VCID. Targeting miR‐15a/16‐1 is a novel therapeutic approach for the treatment of VCID. Abstract : Genetic deletion of miR‐15a/16‐1 promotes the recovery of neurobehavioral functions and alleviates cerebral white and grey matter injury after vascular cognitive impairment and dementia (VCID). Mechanistically, deficiency of the miR‐15a/16‐1 gene preserves AKT3 and IL‐10RA activity in VCID mice. Intranasal delivery of AKT3 and IL‐10RA siRNA‐loaded nanoparticles partially blocks brain protection and functional recovery in miR‐15a/16‐1 KO mice after VCID.